ETNOMATEMATIKA: EKSPLORASI PERMAINAN ENGKLEK SEBAGAI MEDIA PEMBELAJARAN MATEMATIKA (ETNOMATHEMATICS: EXPLORATION OF ENGKLEK GAMES AS A MATHEMATICS LEARNING MEDIA) - hardi - tambunan; Jonathan Simanjuntak (Universitas Quality, 2021)
The main purpose of this study is to explore the ethnomathematics that exist in the traditional game, namely the engklek game. The research method used in this study is a qualitative research method with an ethnographic approach. The data collection technique is done by triangulation (combined) through direct observation, documentation, and literature study through journals on the internet. The data analysis technique used is descriptive analysis. The author chose to conduct research at SDN 101916 Araskabu (the engklek game is still being cultivated) and SMP N 6 in the application of engklek as a medium for learning mathematics. Based on the results of research and discussion, it can be concluded that in the traditional engklek game there is ethnomathematics. The ethnomathematics is obtained based on several aspects of the engklek game, namely based on the ethnomathematical game area contained in it, namely flat shapes, number lines, congruence and similarity, nets, and reflexes. In the Gaco form, the ethnomathematics contained in it is a flat-built mathematical element. Meanwhile, based on the determination of the player's lineage, there are ethnomathematics which are opportunities, and based on the rules of the ethnomathematics engklek game contained therein, namely logical concepts related to implications. By applying the traditional engklek game as a learning medium, students will be interested and motivated in learning mathematics.